High seroprevalence of Borrelia miyamotoi antibodies in forestry workers and individuals suspected of human granulocytic anaplasmosis in the Netherlands. Issue 5 (6th September 2014) - Jahfari, S.; Herremans, T.; Platonov, A. E.; Kuiper, H.; Karan, L. S.; Vasilieva, O.; Koopmans, M. P. G.; Hovius, J. W. R.; Sprong, H.
Abstract Substantial exposure to Borrelia miyamotoi occurs through bites from Ixodes ricinus ticks in the Netherlands, which also transmit Borrelia burgdorferi sensu lato and Anaplasma phagocytophilum. Direct evidence for B. miyamotoi infection in European populations is scarce. A flu‐like illness with high fever, resembling human granulocytic anaplasmosis, has been attributed to B. miyamotoi infections in relatively small groups. Borrelia miyamotoi infections associated with chronic meningoencephalitis have also been described in case reports. Assuming that an IgG antibody response against B. miyamotoi antigens reflects (endured) infection, the seroprevalence in different risk groups was examined. Sera from nine out of ten confirmed B. miyamotoi infections from Russia were found to be positive with the recombinant antigen used, and no significant cross‐reactivity was observed in secondary syphilis patients. The seroprevalence in blood donors was set at 2.0% (95% CI 0.4–5.7%). Elevated seroprevalences in individuals with serologically confirmed, 7.4% (2.0–17.9%), or unconfirmed, 8.6% (1.8–23%), Lyme neuroborreliosis were not significantly different from those in blood donors. The prevalence of anti‐B. miyamotoi antibodies among forestry workers was 10% (5.3–16.8%) and in patients with serologically unconfirmed but suspected human granulocytic anaplasmosis was 14.6% (9.0–21.8%); these were significantly higher compared with the seroprevalence in blood donors. Our findings indicate that infections with B. miyamotoi occur in tick‐exposed individuals in the Netherlands. In addition, B. miyamotoi infections should be considered in patients reporting tick bites and febrile illness with unresolved aetiology in the Netherlands, and other countries where I. ricinus ticks are endemic.